PENGARUH FREE CASH FLOW DAN FINANCIAL LEVERAGE TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Jihana Safira Tualeka; Tenriwaru Tenriwaru; Ummu Kalsum (SIMAK, 2020)
This research aimed to examine whether free cash flow and financial leverage affected profit management and whether good corporate governance as a moderating variable moderated the effect of free cash flow and financial leverage on profit management on textile and garment companies listed on the Indonesia Stock Exchange in the period 2016-2018. This study used sample of 16 companies from the textile and garment listed on the Indonesia Stock Exchange for the period of 2016-2018, and used a purposive sampling technique. Based on the results of research conduct shows that free cash flow has a negative and significant effect on earnings management. Financial leverage has a negative and not significant effect on earnings management. Good corporate governance can moderate or strengthen the influence between free cash flow and profit management. And good corporate governance can moderate or strengthen the influence between financial leverage and profit management.